ANXIETY PORTRAYED IN THE NOVEL GROWN BY TIFFANY D. JACKSON - Paramitha, Vinka Pradnya (Linguistics and Literature Journal, 2025)
The study entitled “Anxiety Portrayed in the Novel Grown by Tiffany D. Jackson” was conducted to examine the issue of anxiety of the main character. The study aims to describe the anxiety of the main character and how she overcomes it. The object of this study is the novel Grown (2020) by Tiffany D. Jackson. The study is analyzed based on Sigmund Freud’s psychoanalysis theory, which includes anxiety (1933) and defence mechanisms (1964). The study is conducted using a qualitative method in which the data were taken from the narratives of the novel. The results depicted three anxieties: realistic anxiety, moral anxiety, and neurotic anxiety, and how the main character overcomes the anxiety through six types of defence mechanisms: repression, denial, projection, displacement, reaction formation, and sublimation.Keywords: anxiety, defense Mechanisms, Psychoanalysis